1999
DOI: 10.1074/jbc.274.16.10911
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclooxygenase-2 Gene Expression by p53

Abstract: Oncogenes enhance the expression of cyclooxygenase (Cox)-2, but interactions between tumor suppressor genes and Cox-2 have not been studied. In the present work, we have compared the levels of Cox-2 and the production of prostaglandin E 2 in mouse embryo fibroblasts that do not express any p53 ((10)1) versus the same cell line ((10.1)Val5) engineered to overexpress wildtype (wt) p53 at 32°C or mutant p53 at 39°C. Cells expressing wt p53 showed about a 10-fold decrease in synthesis of prostaglandin E 2 compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
184
5
4

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(203 citation statements)
references
References 42 publications
(34 reference statements)
10
184
5
4
Order By: Relevance
“…With respect to Pol II inhibition, several mechanisms have been documented (Figure 3). These include repression of transcription activators by physical interaction with and preventing them from activating the promoter [111][112][113][114][115][116] or by displacing them from the adjusting or overlapping binding sites within the promoter, [117][118][119][120] interference with the assembly of transcription machinery, 7,121 repression through the recruitment of histone deacetylase (HDAC) and, possibly, other chromatin modifying factors, [122][123][124] and finally through novel REs with the unique architecture that dictates the outcome of p53 binding. 14,125 Combination of two of the above mechanisms has been also documented.…”
Section: Transcription Regulation By P53mentioning
confidence: 99%
“…With respect to Pol II inhibition, several mechanisms have been documented (Figure 3). These include repression of transcription activators by physical interaction with and preventing them from activating the promoter [111][112][113][114][115][116] or by displacing them from the adjusting or overlapping binding sites within the promoter, [117][118][119][120] interference with the assembly of transcription machinery, 7,121 repression through the recruitment of histone deacetylase (HDAC) and, possibly, other chromatin modifying factors, [122][123][124] and finally through novel REs with the unique architecture that dictates the outcome of p53 binding. 14,125 Combination of two of the above mechanisms has been also documented.…”
Section: Transcription Regulation By P53mentioning
confidence: 99%
“…In 1999, Subbaramaiah et al (1999) reported that expression of p53 at high levels in mouse fibroblasts repressed Cox-2, and proposed that p53 may compete with TATAbinding proteins for binding to the COX-2 promoter. More recently, Han et al (2002) demonstrated an opposite effect, with namely a physiological, p53-dependent increase in Cox-2 expression in response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies demonstrate that wild-type p53 overexpression leads to increased COX-2 levels (Han et al, 2002;Corcoran et al, 2005), other studies report opposite effects where p53 inhibits COX-2 transcription (Subbaramaiah et al, 1999;Liu et al, 2005). However, there is general agreement in the literature regarding the effect of COX-2 on p53 activity.…”
Section: Introductionmentioning
confidence: 99%